Factors associated with durable EFS in adult B-cell ALL patients achieving MRD-negative CR after CD19 CAR T-cell therapy - Hay, Kevin A; Gauthier, Jordan; Hirayama, Alexandre V; Voutsinas, Jenna M; Wu, Qian; Li, Daniel; Gooley, Ted A; Cherian, Sindhu; Chen, Xueyan; Pender, Barbara S; Hawkins, Reed M; Vakil, Aesha; et al. (Blood, 2019)
Autologous T cells engineered to express a CD19-specific chimeric antigen receptor (CAR) have produced impressive minimal residual disease-negative (MRD-negative) complete remission (CR) rates in patients with relapsed/refractory B-cell acute lymphoblastic leukemia (B-ALL). However, the factors associated with durable remissions after CAR T-cell therapy have not been fully elucidated. We studied patients with relapsed/refractory B-ALL enrolled in a phase 1/2 clinical trial evaluating lymphodepletion chemotherapy followed by CD19 CAR T-cell therapy at our institution. Forty-five (85%) of 53 patients who received CD19 CAR T-cell therapy and were evaluable for response achieved MRD-negative CR by high-resolution flow cytometry. With a median follow-up of 30.9 months, event-free survival (EFS) and overall survival (OS) were significantly better in the patients who achieved MRD-negative CR compared with those who did not (median EFS, 7.6 vs 0.8 months; < .0001; median OS, 20.0 vs 5.0 months; = .014). In patients who achieved MRD-negative CR by flow cytometry, absence of the index malignant clone by deep sequencing was associated with better EFS ( = .034). Stepwise multivariable modeling in patients achieving MRD-negative CR showed that lower prelymphodepletion lactate dehydrogenase concentration (hazard ratio [HR], 1.38 per 100 U/L increment increase), higher prelymphodepletion platelet count (HR, 0.74 per 50 000/μL increment increase), incorporation of fludarabine into the lymphodepletion regimen (HR, 0.25), and allogeneic hematopoietic cell transplantation (HCT) after CAR T-cell therapy (HR, 0.39) were associated with better EFS. These data allow identification of patients at higher risk of relapse after CAR T-cell immunotherapy who might benefit from consolidation strategies such as allogeneic HCT. This trial was registered at www.clinicaltrials.gov as #NCT01865617.